Mutational analysis of DNMT3A improves the prognostic stratification of patients with acute myeloid leukemia. Issue 4 (27th January 2023) - Wakita, Satoshi; Marumo, Atsushi; Morita, Kaoru; Kako, Shinichi; Toya, Takashi; Najima, Yuho; Doki, Noriko; Kanda, Junya; Kuroda, Junya; Mori, Shinichiro; Satake, Atsushi; Usuki, Kensuke; et al.
Abstract: Nucleophosmin1 ( NPM1 ) mutations are the most frequently detected gene mutations in acute myeloid leukemia (AML) and are considered a favorable prognostic factor. We retrospectively analyzed the prognosis of 605 Japanese patients with de novo AML, including 174 patients with NPM1 ‐mutated AML. Although patients with NPM1 ‐mutated AML showed a high remission rate, this was not a favorable prognostic factor for overall survival (OS); this is contrary to generally accepted guidelines. Comprehensive gene mutation analysis showed that mutations in codon R882 of DNA methyltransferase 3A ( DNMT3A R882 mutations) were a strong predicative factor indicating poor prognosis in all AML ( p < 0.0001) and NPM1 ‐mutated AML cases ( p = 0.0020). Furthermore, multivariate analysis of all AML cases showed that DNMT3A R882 mutations and the co‐occurrence of internal tandem duplication in FMS‐like tyrosine kinase 3 ( FLT3 ‐ITD), NPM1 mutations, and DNMT3A R882 mutations (triple mutations) were independent factors predicting a poor prognosis related to OS, with NPM1 mutations being an independent factor for a favorable prognosis (hazard ratios: DNMT3A R882 mutations, 1.946; triple mutations, 1.992, NPM1 mutations, 0.548). Considering the effects of DNMT3A R882 mutations and triple mutations on prognosis and according to the classification of NPM1 ‐mutated AML into three risk groups based on DNMT3A R882 / FLT3 ‐ITD genotypes, we achieved the improved stratification of prognosis ( p < 0.0001). We showed that DNMT3A R882 mutations are an independent factor for poor prognosis; moreover, when confounding factors that include DNMT3A R882 mutations were excluded, NPM1 mutations were a favorable prognostic factor. This revealed that ethnological prognostic discrepancies in NPM1 mutations might be corrected through prognostic stratification based on the DNMT3A status. Abstract : Our new stratification system using FLT3 ‐ITD/ DNMT3A R882 genotypes predicted the recurrence of NPM1 mutation‐positive acute myeloid leukemia more clearly than did the ELN2017 classification and succeeded in extracting patients with a poor prognosis.